Clinical utility of α-glutathione S-transferase in hepatocellular injury: a review synthesis from clinical studies - John Derrick Chan (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Early detection of hepatocellular injury remains a significant clinical challenge due to the limitations of conventional biomarkers such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), which often rise only after substantial liver damage has occurred. α-Glutathione S-transferase (α-GST), a cytosolic enzyme highly expressed in hepatocytes, has emerged as a promising biomarker due to its rapid release and short plasma half-life, enabling earlier detection of liver injury. Aim This study aimed to systematically review and synthesize clinical evidence on the diagnostic and prognostic utility of α-GST in detecting hepatocellular injury across various clinical contexts. Methods A systematic literature review was conducted using major databases, including PubMed/MEDLINE, Scopus, Web of Science, Embase, and the Cochrane Library, covering studies published from 1988 to 2023. Eligible studies included human subjects with confirmed or suspected hepatocellular injury and reported α-GST measurements in serum or plasma alongside comparator biomarkers such as ALT and AST. Data were extracted and analyzed qualitatively due to heterogeneity in study design and outcomes. Results Evidence indicates that α-GST demonstrates superior temporal sensitivity compared to conventional aminotransferases, with earlier elevation in acute liver injury, ischemia–reperfusion injury, and drug-induced liver injury. It also detects subclinical hepatocellular damage in chronic liver diseases, including hepatitis C, even when ALT levels remain normal. Reported diagnostic performance shows sensitivity ranging from 78 to 92% and specificity from 80 to 95%, particularly when measured using enzyme-linked immunosorbent assays (ELISA). Additionally, α-GST correlates with histological markers of hepatocellular necrosis and disease severity. However, variability in assay methods, lack of standardized cut-off values, and limited large-scale validation studies constrain its routine clinical application. Conclusion α-GST is a highly sensitive and early biomarker of hepatocellular injury with significant potential to complement traditional liver function tests. While current evidence supports its clinical utility across diverse liver injury contexts, further standardization, multicenter validation, and integration into multimarker diagnostic approaches are necessary to facilitate its adoption in routine hepatology practice.